2001
DOI: 10.1086/320871
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Bacterial, Viral, and Fungal Infections in Adult Recipients of Bone Marrow Transplants

Abstract: The epidemiology of infections was studied in a retrospective cohort of 446 recipients of bone marrow transplants (BMTs; 92 of which were allogeneic and 354 of which were autologous) during 1993--1996. Infections that were microbiologically documented in 274 recipients included bacteremia, urinary tract infections, cytomegalovirus viremia, fungemia, invasive aspergillosis, and catheter-related infections. During the period of neutropenia, no differences were found between recipients of allogeneic BMTs and reci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
72
6
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 13 publications
16
72
6
5
Order By: Relevance
“…16,17 Studies from Asian countries like Israel have observed an increasing incidence of fungal isolates from BMT units 18 similar to the data from our center (19.7%). Infections due to Candida infections have decreased over the years probably due to the early institution of fluconazole for the treatment of febrile neutropenia.…”
Section: Discussionsupporting
confidence: 86%
“…16,17 Studies from Asian countries like Israel have observed an increasing incidence of fungal isolates from BMT units 18 similar to the data from our center (19.7%). Infections due to Candida infections have decreased over the years probably due to the early institution of fluconazole for the treatment of febrile neutropenia.…”
Section: Discussionsupporting
confidence: 86%
“…3,6,8,18,23 The majority of disagreements related to difficulties in the evaluation of relapsed or persistent disease, GVHD and infectious diseases. Infection is a major cause of death in BMT patients 11,[23][24][25][26][27][28] and accounts for most of the major disagreements (63%) in our study.…”
Section: Discussionmentioning
confidence: 86%
“…However, in this study, such an influence of contaminants is less likely since (1) our definition of BSI with common skin contaminants was rigorous (at least two positive consecutive cultures or two positive cultures within 72 h of one another) and in accordance with that used by other investigators; 1,4,6,16,[38][39][40][41][42][43] (2) the cultures were obtained in response to an indication of infection as opposed to carried out for surveillance; and (3) the common isolation of coagulase-negative staphylococcal from the blood is consistent with other studies. 2,6,44,45 It is more likely that the high proportion of coagulase-negative staphylococcal BSI was due to several factors including the presence of indwelling central venous catheters in virtually all of the patients in the early post-HSCT phase and the universal use of prophylaxis with fluoroquinolones. Finally, the group of patients undergoing reduced intensity HSCT was small, comprising 5% of the total cohort.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 It has been observed to occur in 13-60% of HSCT recipients. 1,[3][4][5][6][7][8][9][10] The differences in findings of these studies is likely due to factors such as different study designs, study populations, conditioning regimens and prophylactic antibiotic protocols.…”
Section: Introductionmentioning
confidence: 99%